EULAR/PReS endorsed consensus criteria for the classification of childhood vasculitides. Issue 7 (1st December 2005) - Ozen, S; Ruperto, N; Dillon, M J; Bagga, A; Barron, K; Davin, J C; Kawasaki, T; Lindsley, C; Petty, R E; Prieur, A M; Ravelli, A; Woo, P
Abstract : Background: There has been a lack of appropriate classification criteria for vasculitis in children. Objective: To develop a widely accepted general classification for the vasculitides observed in children and specific and realistic classification criteria for common childhood vasculitides (Henoch-Schönlein purpura (HSP), Kawasaki disease (KD), childhood polyarteritis nodosa (PAN), Wegener's granulomatosis (WG), and Takayasu arteritis (TA)). Methods: The project was divided into two phases: (1) the Delphi technique was used to gather opinions from a wide spectrum of paediatric rheumatologists and nephrologists; (2) a consensus conference using nominal group technique was held. Ten international experts, all paediatricians, met for the consensus conference. Agreement of at least 80% of the participants was defined as consensus. Results: Consensus was reached to base the general working classification for childhood vasculitides on vessel size. The small vessel disease was further subcategorised into "granulomatous" and "non-granulomatous." Final criteria were developed to classify a child as HSP, KD, childhood PAN, WG, or TA, with changes introduced based on paediatric experience. Mandatory criteria were suggested for all diseases except WG. Conclusions: It is hoped that the suggested criteria will be widely accepted around the world because of the reliable techniques used and the international and multispecialist composition of the expert group involved.